Scrap Poster sebagai Media Kampanye Sosial Anti Narkoba di SMA Negeri Cirebon (Faculty of Communications Science, Dr. Soetomo University, 2018)
Indonesia is undergoing drug emergency. Various efforts have been made by BNN to reduce drug abuse throughout Indonesia is no exception in the city of Cirebon. Nevertheless drug users in Cirebon City remain high and most are teenagers. This is because teens are more likely to try before becoming addicted. This study aims to determine the effect of social abuse drug campaign on the attitude of the students in 9 SMA Negeri Kota Cirebon regarding the misuse of drugs. The media used in this research is scrap poster, namely posters made of various kinds of waste used. The results of the research as follows: Message Intensity Variable (X1) has an influence of 30.2% on students 'attitudes about the dangers of drugs, message display variables (X2) has an effect of 39.6% on students' attitudes about the dangers of drugs, message content variables (X3) has an effect of 42.8% on students' attitudes about the dangers of drugs. While the influence arising from the three variables that display message (X1), display message variables (X2) and variable content message (X3) on attitude of students of SMA Negeri in Cirebon by 48%.Keywords: Drugs, Social Campaigns, scrap poster